CEMARAN PESTISIDA KLOR-ORGANIK DALAM AIR DANAU BUYAN BULELENG BALI - Putra Manuaba, I. B. (Jurnal Kimia (Journal of Chemistry); Vol. 1, No. 2 Juli 2007)
The use of pesticide around the Lake Buyan is inevitable. This will introduce pollutant to either the soil or lake water. In this research, organochlorine pesticide residual contamination in water was investigated. Lake Buyan is used as the investigation model, since there were a lot of pressure to the lake as a consequence of increasing human activities such as tourism, hotel and restaurant, and farming. This is an expost facto study with Analytical Cross Sectional Study design, within two step activities, i.e. field study in order to gain sampling zone and obtaining sample needed. Followed by laboratory works in order to obtain pesticide residual contamination on water. Sample preparation for this purposed was carried out following a standard method. Gas Chromathographi was employed in order to gain the pesticide contaminant. Positive organochlorine pesticide contaminant, i.e. DDT and chlorotalonile were observed from 55 sampling point of water taken from five sampling zones. DDT in the water was 5.02 ppb which is still bellow the maximum level of 42 ppb. Chlorotalonile in water was 1.99 ppb. There is no threshold value of these pesticide residues on the Government regulation, however, this contamination is still bellow the RfD which is 15 ppb.
Keywords: organochlorine pesticide, residual contaminant, expost facto